Tingkat Pengetahuan Pelaku Usaha Mikro dan Kecil terhadap Halal Self Declare di Pasar Sunday Morning Simpang GOR Satria Purwokerto, Jawa Tengah - Syska, Kavadya (Journal of Agricultural and Biosystem Engineering Research, 2023)
Halal is one of the standards that must be met to provide protection for the halalness of a product that is consumed or used by the public. As a Muslim, it is important to understand the halal status of a product that will be consumed or used. However, not all consumers understand the halal status of the products they are going to consume, so regulations are needed to regulate and ensure that products circulating in the community have a clear halal status. One of the ways to carry out halal certification for Micro and Small Enterprises is by halal self-declaring. The purpose of this study was to find out the knowledge of small micro business actors about halal self-declare at the Satria Purwokerto GOR Intersection. The method used in this research is quantitative method. The data were obtained from the results of direct distribution of questionnaires, observations, and interviews with SMEs actors in the Simpang GOR Satria Purwokerto area with a questionnaire tool. The data obtained using quantitative analysis. data analysis using descriptive analysis and logistic regression. Interview data were analyzed using Microsoft excel software. The results of the study show that the knowledge of micro and small entrepreneurs at the GOR Satria Purwokerto Intersection is high. The results of the descriptive analysis show that the variables age, religion, education, influence, halal knowledge, networking and outreach are significant to the level of knowledge of micro and small business actors regarding halal self-declare at the Sunday Morning Market, Simpang GOR Satria Purwokerto.